Laser‐Induced Nano‐Functional Surfaces for Enhanced SERS Performance - Hardik Vaghasiya; Paul‐Tiberiu Miclea (Advanced Materials Interfaces)
Abstract Nanostructured metal surfaces play a crucial role in sensing applications, particularly in Surface‐Enhanced Raman Spectroscopy (SERS). In this study, laser‐induced periodic surface structures (LIPSS) are fabricated on silicon substrates using femtosecond laser irradiation to investigate their formation mechanisms and impact on Raman signal enhancement. By systematically varying the laser fluence and pulse number, their effects are examined on LIPSS periodicity and, consequently, SERS performance. The results reveal that increasing laser fluence from 0.80 to 1.40 J/cm2 significantly reduces LIPSS periodicity due to enhanced Surface Plasmon Polaritons (SPPs) excitation and energy redistribution. LIPSS exhibit elongated elliptical structures at lower pulse numbers, which gradually transition into circular patterns with increasing pulses, driven by electric field redistribution and interference effects. The influence of LIPSS on SERS is systematically analyzed using a thiophenol solution to evaluate Raman signal sensitivity. The results demonstrate that precisely tuned periodicity and depth of LIPSS significantly enhance SERS signals by optimizing localized electromagnetic fields and plasmonic resonance effects. Notably, LIPSS with a periodicity of ∼795 nm exhibited the highest enhancement due to the resonant coupling of SPPs with the excitation laser, while optimal depths (∼352–547 nm) balanced hotspot density and plasmonic efficiency.